Dual-Track Model for Resolving Disputes Over Late Payment of Soccer Players' Salaries (Study of Labor Law and FIFA Regulations) - Gentar Restu; Otong Syuhada; Zuraidah (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2025)
Cases of late payment of salaries by football clubs to professional football players often raise confusion regarding the legal forum that should be chosen, namely whether the dispute should be resolved through labor law or FIFA regulations. This study aims to formulate a dual-track model for resolving wage payment disputes through the perspective of national labor law and FIFA regulations. The method used is a normative legal approach combining the statute approach and case approach. This study’s innovation offers a dual-track dispute resolution model for football players’ wages, combining national mechanisms (labor law and Resolution of Industrial Relations) and international mechanisms (FIFA regulations and DRC). The research findings indicate that dispute resolution through Resolution of Industrial Relations tends to be slow, while FIFA's DRC is faster but less accessible for local players. This study proposes a harmonious dual-track model by integrating national and international.